Charter slips 02: Berkshire (parishes beginning H-Y) - Bodleian Libraries Special Collections (University of Oxford, 2022)
Handwritten summaries in English of charters and other documents, mostly in Latin but occasionally in English or French, acquired by the Bodleian Library after c. 1878, created by mostly anonymous staff of the library between about 1878 and the late twentieth century. The summaries are organized by county and within county by parish and relate to documents mostly produced between about 1200 and 1800. Although there are some so-called 'foreign charters' the great majority of the material relates to the British Isles and particularly to England, with particularly extensive collections for Berkshire, Buckinghamshire and Oxfordshire.